Zeolitic imidazolate framework (ZIF)-derived, hollow-core, nitrogen-doped carbon nanostructures for oxygen-reduction reactions in PEFCs - Palaniselvam, Thangavelu; Biswal, Bishnu P.; Banerjee, Rahul; Kurungot, Sreekumar (Chemistry-A European Journal, 2013)
The facile synthesis of a porous carbon material that is doped with iron-coordinated nitrogen active sites (FeNC-70) is demonstrated by following an inexpensive synthetic pathway with a zeolitic imidazolate framework (ZIF-70) as a template. To emphasize the possibility of tuning the porosity and surface area of the resulting carbon materials based on the structure of the parent ZIF, two other ZIFs, that is, ZIF-68 and ZIF-69, are also synthesized. The resulting active carbon material that is derived from ZIF-70, that is, FeNC-70, exhibits the highest BET surface area of 262m2g-1 compared to the active carbon materials that are derived from ZIF-68 and ZIF-69. The HR-TEM images of FeNC-70 show that the carbon particles have a bimodal structure that is composed of a spherical macroscopic pore (about 200nm) and a mesoporous shell. X-ray photoelectron spectroscopy (XPS) reveals the presence of Fe-N-C moieties, which are the primary active sites for the oxygen-reduction reaction (ORR). Quantitative estimation by using EDAX analysis reveals a nitrogen content of 14.5wt.%, along with trace amounts of iron (0.1wt.%), in the active FeNC-70 catalyst. This active porous carbon material, which is enriched with Fe-N-C moieties, reduces the oxygen molecule with an onset potential at 0.80V versus NHE through a pathway that involves 3.3-3.8e- under acidic conditions, which is much closer to the favored 4e- pathway for the ORR. The onset potential of FeNC-70 is significantly higher than those of its counterparts (FeNC-68 and FeNC-69) and of other reported systems. The FeNC-based systems also exhibit much-higher tolerance towards MeOH oxidation and electrochemical stability during an accelerated durability test (ADT). Electrochemical analysis and structural characterizations predict that the active sites for the ORR are most likely to be the insitu generated NFeN2+2/C moieties, which are distributed along the carbon framework.
Keywords: Doping; Electrochemistry; metal-organic frameworks; Nanostructures; oxygen-reduction reaction

Zinc ion interactions in a two-dimensional covalent organic framework based aqueous zinc ion battery - Mohammed, Abdul Khayum; Ghosh, Meena; Vijayakumar, Vidyanand; Halder, Arjun; Nurhuda, Maryam; Kumar, Sushil; Addicoat, Matthew; Kurungot, Sreekumar; Banerjee, Rahul (Chemical Science, 2019)
<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">The two-dimensional structural features of covalent organic frameworks (COFs) can promote the electrochemical storage of cations like H<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">, Li<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">, and Na<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> through both faradaic and non-faradaic processes. However, the electrochemical storage of cations like Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> ion is still unexplored although it bears a promising divalent charge. Herein, for the first time, we have utilized hydroquinone linked β-ketoenamine COF acting as a Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> anchor in an aqueous rechargeable zinc ion battery. The charge-storage mechanism comprises of an efficient reversible interlayer interaction of Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> ions with the functional moieties in the adjacent layers of COF (−182.0 kcal mol<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">). Notably, due to the well-defined nanopores and structural organization, a constructed full cell, displays a discharge capacity as high as 276 mA h g<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> at a current rate of 125 mA g<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">.

Zinc-air batteries catalyzed using Co3O4 nanorod-supported N-doped entangled graphene for oxygen reduction reaction - Manna, Narugopal; Singh, Santosh K.; Kharabe, Geeta Pandurang; Torris, Arun; Kurungot, Sreekumar (ACS Applied Energy Materials, 2021)
The work reported here deals with the development of an efficient non-platinum electrocatalyst for electrochemical oxygen reduction reaction (ORR) through a sequential pathway involving hydrothermal treatment followed by freeze-drying to build the desired structural architecture of the catalyst. The designed catalyst (Co3O4/nitrogen-doped entangled porous 3D graphene (NEGF)), which contains Co3O4 nanorods anchored on the surface of three-dimensional (3D)-structured N-doped graphene, was found to display higher ORR activity during single-electrode testing and demonstrate a Zn-air battery (ZAB) system. Under the hydrothermal treatment at 180 degrees C, in the presence of ammonia, nitrogen was doped into the carbon framework of graphene, which subsequently formed a self-assembled entangled 3D structure of graphene after freeze-drying. The hydrothermal treatment and freeze-drying processes were found to play vital roles in tuning the morphological and structural features of the catalyst. The doped nitrogen, apart from its favorable contribution toward ORR, helped facilitate efficient dispersion of oxide nanorods on graphene. Co3O4/NEGF displayed remarkable ORR activity in 0.1 M KOH solution, as evident from the 60 mV onset potential shift compared to the state-of-the-art Pt/C catalyst and the Tafel slope value of 74 mV dec(-1) vs 68 mV dec(-1) for Pt/C. The ZAB fabricated by employing Co3O4/NEGF as the cathode catalyst was found to be an efficient competitor for the system based on the Pt/C cathode. This high performance has been credited to the controlled interplay of the governing factors such as the interfacial interactions leading to the efficient dispersion of metal oxide nanorods, increased catalyst surface area, the cooperative effect arising from the defects present in the N-doped porous 3D graphene, and the synergetic interactions operating in the system.
Keywords: cobalt-oxide nanorod; freeze-drying; hydrothermal; N-doped entangled graphene; oxygen reduction reaction; zinc-air battery